Methods and technologies for the implementation of pedagogical games in the system of preschool education - Jumanova Ozoda Eshpoʻlat qizi (International Journal on Orange Technologies, 2020)
Organization of gaming activities in preschool organizations, the tasks of the teacher, types of games, methods and technologies of games, forms of organization of games in the world, the basic principles of games, about the functions of the game.